(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
This paper explores the critical importance of Health Insurance Portability and Accountability Act (HIPAA) compliance in medical record management, focusing on safeguarding patient privacy and ensuring data security. The HIPAA Privacy Rule and Security Rule are examined, highlighting key provisions and requirements for covered entities and business associates. Emphasis is placed on patient privacy rights, consent requirements, and security safeguards for protected health information (PHI). Electronic Health Records (EHRs) are discussed in the context of HIPAA compliance, addressing challenges and strategies for securely storing, accessing, and sharing electronic medical records. Additionally, the role of Business Associate Agreements (BAAs) in maintaining HIPAA compliance when working with third-party service providers is explored. Enforcement mechanisms, penalties for non-compliance, and best practices for HIPAA compliance are also outlined. This paper aims to provide healthcare organizations with a comprehensive understanding of HIPAA regulations and practical guidance for ensuring compliance in medical record management.